2003
DOI: 10.1016/s0954-6111(03)00249-x
|View full text |Cite
|
Sign up to set email alerts
|

Health related quality of life in individuals with asthma related symptoms

Abstract: HRQoL measured using EQ-5D is substantially reduced in respondents with respiratory symptoms enabling use of the instrument in inter-disease comparisons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
20
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 18 publications
6
20
0
Order By: Relevance
“…The QoL scores in four domains significantly correlated with education, age, and marital status. Similar results concerning the influence of age and education on the QoL scores were obtained by Oguzturk et al (2005), Hazell et al (2003), Ferreira et al (2010) and Laforest et al (2005). Nevertheless, the analysis of the logistic regression revealed that women had twice greater chances for a positive QoL assessment than men.…”
Section: Discussionsupporting
confidence: 76%
“…The QoL scores in four domains significantly correlated with education, age, and marital status. Similar results concerning the influence of age and education on the QoL scores were obtained by Oguzturk et al (2005), Hazell et al (2003), Ferreira et al (2010) and Laforest et al (2005). Nevertheless, the analysis of the logistic regression revealed that women had twice greater chances for a positive QoL assessment than men.…”
Section: Discussionsupporting
confidence: 76%
“…Studies have shown that asthma, eczema and rhinitis have a negative impact on quality of life (QoL) [8][9][10][11][12][13][14][15][16]. Consistent and successful avoidance of the offending foods, however, limits the influence on individuals' physical health.…”
Section: Introductionmentioning
confidence: 99%
“…Extrapolating figures from a study comparing the respiratory diseasespecific St George's respiratory questionnaire (SGRQ), 27 with EQ-5D, a clinically significant change in EQ-5Dindex would be 0.08 and in EQ-5Dvas 9.08. 28 The MID for EQ-5Dvas has not been widely studied, but one estimate is as low as 3.0. 29 There are few reports, so far, of what changes are important in a general population, which includes a majority of healthy people in addition to those with a number of different single and multiple pathologies.…”
mentioning
confidence: 99%